PVDF Composite Membranes with Hydrophobically-Capped CuONPs for Direct-Contact Membrane Distillation - César Saldías; Claudio A. Terraza; Angel Leiva; Joachim Koschikowski; Daniel Winter; Alain Tundidor-Camba; Rudy Martin-Trasanco (Nanomaterials, 2021)
Water scarcity is an imminent problem that humanity is beginning to attempt to solve. Among the several technologies that have been developed to mitigate water scarcity, membrane distillation is of particular note. In the present work, CuO nanoparticles capped with 1-octanethiol (CuONPs@CH) or 1H,1H,2H,2H-perfluorodecanethiol (CuONPs@CF) are prepared. The nanoparticles are characterized by FT-IR and TGA methods. Two weight losses are observed in both cases, with the decomposition of the organic fragments beginning at 158 °C and 230 °C for CuONPs@CF and CuONPs@CH, respectively. Flat sheet PVDF composite membranes containing nanoparticles are prepared by the casting solution method using nanoparticle concentrations that ranged between 2–20% with a non-woven polyester fabric as support. The obtained membranes showed a thickness of 240 ± 40 μm. According to water contact angle (87° for CuONPs@CH and 95° for CuONPs@CF, both at 10% w.t) and roughness (12 pixel for CuONPs@CH and 14 pixels for CuONPs@CF, both at 10% w.t) determinations, the hydrophobicity of membranes changed due to a decrease in surface energy, while, for naked CuONPs, the roughness factor represents the main role. Membranes prepared with capped nanoparticles showed similar porosity (60–64%). SEM micrographs show asymmetric porous membranes with a 200-nm surface pore diameter. The largest finger-like pores in the membranes prepared with CuONPs, CuONPs@CH and CuONPs@CF had values of 63 ± 10 μm, 32 ± 8 μm, and 45 ± 10 μm, respectively. These membranes were submitted to a direct contact membrane distillation module and flux values of 1.8, 2.7, and 3.9 kg(m2·h)−1 at ΔT = 30 °C were obtained for the CuONPs, CuONPs@CH, and CuONPs@CF, respectively. The membranes showed 100% salt rejection during the testing time (240 min).